PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN DAN DAMPAKNYA TERHADAP LOYALITAS DI RUMAH SAKIT NATAR MEDIKA - Hairudin; Oktaria, Eka Travilta (Universitas Putera Batam, 2024)
This study aims to examine the effect of patient satisfaction variables in mediating the effect of service quality and health facilities on patient loyalty. Respondents were in patients who were in class 2 and 3. There were 225 questionnaires that could be collected. Based on the PLS-SEM analysis, it can be concluded that the quality of health services directly has a significant positive effect on patient satisfaction; health facilities directly have a significant positive effect on patient satisfaction; the quality of health services directly has a significant positive effect on patient loyalty; patient satisfaction directly has a significant positive effect on patient loyalty; Health facilities directly have a significant positive effect on patient loyalty; patient satisfaction is positively and significantly able to mediate the quality of health services on patient loyalty; and patient satisfaction positively and significantly able to mediate health facilities to patient loyalty at Natar Medika Hospital.